Delineation of canine parvovirus T cell epitopes with peripheral blood mononuclear cells and T cell clones from immunized dogs - Rimmelzwaan, G. F.; Poelen, M. C. M.; Meloen, R. H.; Carlson, J.; UytdeHaag, F. G. C. M.; Osterhaus, A. D. M. E. (Journal of General Virology, 1990)
Three synthetic peptides derived from the amino acid sequence of VP2 of canine parvovirus (CPV) which were recently shown to represent three distinct T cell epitopes for BALB/c mice could prime BALB/c mice for a CPV-specific proliferative T cell response upon immunization. Proliferative responses of peripheral blood mononuclear cells (PBMC) from CPV-immunized dogs upon stimulation with these and other peptides, covering the major part of the sequence of VP2′, identified the presence of T cell epitopes for this species. Most of these epitopes were recognized by PBMC from only a minority of the dogs tested. With three newly generated canine Thyl+ T cell clones, which recognized CPV antigen in association with major histocompatibility complex class II molecules, two distinct T cell epitopes were identified within the unique sequence of VP1.